Photosynthetic and Chlorophyll Fluorescence Characteristics of Isodon rubescens (Hemsley) H. Hara - Zaiyou, Jian (Sci Rep, 2020)
The ecological and economic cultivation of Isodon rubescens is currently being carried out. The demand of I. rubescens for light intensity should be made clear to estimate whether the environmental conditions of an area are suitable for cultivating I. Rubescens and improve cultivation techniques. The photosynthetic and chlorophyll fluorescence characteristics of I. rubescens were determined with a Li-6400 photosynthesis system and PAM-2500 portable chlorophyll fluorescence apparatus. The results showed that there was no obvious midday depression of photosynthesis in I. rubescens leaves. The light compensation point and light saturation point of I. rubescens leaves were 21.83482 µmol·m(−2)·s(−1) and 802.262 µmol·m(−2)·s(−1), respectively. The CO(2) compensation point and CO(2) saturation point of I. rubescens leaves were 101.7199 µmol·mol(−1) and 1674.514 µmol·mol(−1), respectively. The maximal photochemical efficiency of photosystem II ((Fm-Fo)/Fm) in I. rubescens leaves reached 0.7. The electron transport rate of photosystem II in I. rubescens leaves reached 20 μmol electrons/(m(2)·s). I. rubescens can tolerate intense light above the light compensation point and utilize low light. I. rubescens leaves have a strong photoprotective capacity. I. rubescens can grow in both sunny and shady places. The most important factor affecting photosynthetic efficiency in I. rubescens leaves is the concentration of CO(2) in air.